Antibacterial Filtration Membranes Based on PVDF-co-HFP Nanofibers with the Addition of Medium-Chain 1-Monoacylglycerols - Peer, Petra; Janalikova, Magda; Sedlarikova, Jana; Pleva, Pavel; Filip, Petr; Zelenkova, Jana; Siskova, Alena Opalkova (ACS applied materials & interfaces, 2021)
The efficiency of filtration membranes is substantially lowered by bacterial attachments and potential fouling processes, which reduce their durability and lifecycle. The antibacterial and antifouling properties exhibited by the added materials play a substantial role in their application. We tested a material poly(vinylidene fluoride)-co-hexafluoropropylene (PDVF-co-HFP) based on an electrospun copolymer, where an agent was incorporated with a small amount of ester of glycerol consecutively with caprylic, capric, and lauric acids. Each of these three materials differing in the esters (1-monoacylglycerol, 1-MAG) used was prepared with three weighted concentrations of 1-MAG (1, 2, and 3 wt %). The presence of 1-MAG with an amphiphilic structure resulted in the hydrophilic character of the prepared materials that contributed to the filtration performance. The tested materials (membranes) were characterized with rheological, optical (scanning electron microscopy, SEM), Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), and other methods to evaluate antibacterial and antifouling activities. The pure water flux was 6 times higher than that of the neat PVDF-co-HFP membrane when the added 1-MAG attained only 1 wt %. It was experimentally shown that the PVDF-co-HFP/1-MAG membrane with high wettability improved antibacterial activity and antifouling ability. This membrane is highly promising for water treatment due to the safety of antibacterial 1-MAG additives.
Keywords: wettability; antifouling activity; monoacylglycerols; Staphylococcus aureus; filtration; Filtration; Polyvinyls; Biofouling; antibakteriální látky; monoglyceridy; Microbial Sensitivity Tests; Monoglycerides; fluorokarbonové polymery; Escherichia coli; Fluorocarbon Polymers; membrány umělé; Wettability; nanovlákna; Anti-Bacterial Agents; smáčivost; Biofilms; mikrobiální testy citlivosti; nanofibrous membranes; Nanofibers; poly(vinylidene fluoride)-co-hexafluoropropylene; filtrace; Membranes, Artificial; biofilmy; bioznečištění; polyvinyly; antibacterial activity